2008
DOI: 10.1158/1078-0432.ccr-07-0321
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tuberous Sclerosis Complex-2 Function and Activation of Mammalian Target of Rapamycin Signaling in Endometrial Carcinoma

Abstract: Purpose: The involvement of phosphatase and tensin homologue deleted on chromosome ten (PTEN) in endometrial carcinoma has implicated phosphatidylinositol 3-kinase signaling and mammalian target of rapamycin (mTOR) activation in this disease. Understanding the extent of mTOR involvement and the mechanism responsible for activation is important, as mTOR inhibitors are currently being evaluated in clinical trials for endometrial carcinoma. Although tuberous sclerosis complex 2 (TSC2) is the ''gatekeeper'' for mT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 45 publications
(38 reference statements)
6
44
1
3
Order By: Relevance
“…In one study, western blotting showed a loss of LKB1 expression in 20% of primary tumors, which correlated with activation of the mTOR pathway (Lu et al, 2008). Similarly, we found that 20% of primary tumors showed immunohistochemical loss of LKB1 expression and, furthermore, that loss of the LKB1 protein significantly correlated with tumor stage, and hence, prognosis.…”
Section: Disease Models and Mechanisms Dmmsupporting
confidence: 64%
See 1 more Smart Citation
“…In one study, western blotting showed a loss of LKB1 expression in 20% of primary tumors, which correlated with activation of the mTOR pathway (Lu et al, 2008). Similarly, we found that 20% of primary tumors showed immunohistochemical loss of LKB1 expression and, furthermore, that loss of the LKB1 protein significantly correlated with tumor stage, and hence, prognosis.…”
Section: Disease Models and Mechanisms Dmmsupporting
confidence: 64%
“…endometrial hyperplasias driven by Pten heterozygosity), rapamycin does slow the rate of disease progression, although most studies have not documented shrinkage of tumors of invasive cancers (Milam et al, 2007;Neshat et al, 2001). Interestingly, a recent phase II study of temsirolimus (an ester derivative of rapamycin) in endometrial cancer demonstrated a 26% objective response rate, similar to the 20% rate of endometrial tumors that express low to undetectable levels of the LKB1 protein (Contreras et al, 2008a;Lu et al, 2008). This leads us to speculate that LKB1-AMPK pathway status may be a better predictor of responses to rapalogs than the PI3K-AKT axis, particularly as PI3K…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 93%
“…p-p70S6K is generally used in preference to p-mTOR to assess the tumour response to mTOR antagonists and to predict which tumours may be responsive to such agents (for reviews see Boulay et al (2004); MacKenzie and von Mehren (2007)). Indeed, phosphorylated mTOR has been generally found to be expressed in relatively low numbers of tumours, and several studies make no reference to tumour mTOR expression when assessing the effect of rapamycin and or its analogues (Jaeschke et al, 2002;Gao et al, 2003;Krishnan et al, 2006;El-Salem et al, 2007;Lu et al, 2008; Although the TMA was built with 50 chordomas, the total number described for each antibody represents the number that was possible to analyse. The scoring system employed was as follows: negative in the absence of immunoreactivity, 'low' when the immunoreactivity was unequivocal but less strong than the positive control and 'high' when the immunoreactivity was at least as strong as the positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of human endometrial tumors have shown that $20% are LKB1-negative, and as many as 65% have a functional deficit in the protein (25).…”
Section: Translational Relevancementioning
confidence: 99%
“…Rapalog studies in endometrial cancer have focused primarily on expression of mTOR pathway proteins (44,(52)(53)(54)(55)(56)(57)(58) and cellular responses to mTOR inhibitors (25,52,(59)(60)(61)(62). Several groups have also investigated the role of small-molecule mTOR kinase inhibitors in endometrial cancer cell lines (59,63) and the effects of mTOR inhibitors on mouse models of endometrial cancer (3,(64)(65)(66).…”
Section: Preclinical Studies Of Mtor Inhibition In Endometrial Cancersmentioning
confidence: 99%